2020
DOI: 10.1002/ehf2.12571
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone use is associated with improved outcomes in heart failure with mid‐range ejection fraction

Abstract: Aims Spironolactone has been shown to improve outcomes in patients with heart failure (HF) with reduced ejection fraction (EF). We investigated whether the discharge use of spironolactone could be associated with better long‐term outcomes among patients with HF with mid‐range EF (HFmrEF). Methods and results We analysed HFmrEF (left ventricular EF 40–49%) patients enrolled in the Japanese Cardiac Registry of Heart Failure in Cardiology, which prospectively studied the clinical characteristics, treatments, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
0
14
1
1
Order By: Relevance
“…In line with these findings, the Japanese Cardiac Registry of HF reported that spironolactone at the time of discharge in patients with HFmrEF was associated with lower rates of the composite of all-cause death or HF rehospitalization over 2.2 years [ 30 ]. In a retrospective study from China, the one-year rate of death or HF rehospitalization was lower among patients receiving spironolactone 50 or 25 mg daily compared to untreated patients (21.3% vs. 34.5%, p = 0.014), without a difference between the high and low spironolactone dose groups (21.8% vs. 20.7%, respectively, p = 0.861) [ 28 ].…”
Section: Established Therapiesmentioning
confidence: 82%
“…In line with these findings, the Japanese Cardiac Registry of HF reported that spironolactone at the time of discharge in patients with HFmrEF was associated with lower rates of the composite of all-cause death or HF rehospitalization over 2.2 years [ 30 ]. In a retrospective study from China, the one-year rate of death or HF rehospitalization was lower among patients receiving spironolactone 50 or 25 mg daily compared to untreated patients (21.3% vs. 34.5%, p = 0.014), without a difference between the high and low spironolactone dose groups (21.8% vs. 20.7%, respectively, p = 0.861) [ 28 ].…”
Section: Established Therapiesmentioning
confidence: 82%
“…The mean age of HFmrEF in this study was 54.6 years, lower than reported in developed countries. 14,22 In this report, the mean ages across all EF categories were lower than the mean age across corresponding EF categories in high-income countries. 14 This may reflect differences in HF aetiologies between low-income and high-income countries.…”
Section: Discussionmentioning
confidence: 51%
“…The impact of MRA on outcome in HFmrEF is less well known. A recent study showed that the MRA spironolactone was independently associated with a significant reduction in mortality and HF rehospitalization in HFmrEF 22 . Although patients with HFpEF in our study had lower heart rates, they were more likely to be prescribed beta‐blockers.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…[ 31 ] In another recent study, spironolactone use at discharge after an acute HF episode was associated with better long-term outcomes. [ 32 ] A retrospective analysis of the Digitalis Investigation Group (DIG) suggested a slightly higher decrease in CV death and HF hospitalisation in HFmrEF than HFpEF patients. [ 33 ]…”
Section: Medical Therapymentioning
confidence: 99%